2015
DOI: 10.4103/0976-237x.169840
|View full text |Cite
|
Sign up to set email alerts
|

Oral manifestations of secondary hyperparathyroidism: A case report

Abstract: There are a number of systemic diseases causing bony lesions throughout the body. Secondary hyperparathyroidism (HPT) which is associated with chronic renal failure is one such disorder resulting in a variety of bony changes. Secondary HPT develops when the parathyroid hormone is continuously produced in response to chronic low levels of serum calcium, a situation usually associated with the chronic renal disease. Here we present a case of secondary HPT causing bony changes in maxilla and mandible.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 8 publications
0
14
1
Order By: Relevance
“…3,12 OF/RO usually affects the long bones, ribs, and pelvis, 6 whereas jaw bone involvement is a very rare manifestation of the disease. 12,22 There is no significant sex predilection, and adult patients are the most affected, although our study found a female prevalence (female-tomale ratio 1.66:1) and a 12 year old affected by the lesion. The pathologic process often involves the jaws diffusely, as illustrated in 3 of our reports, possibly leading to severe facial asymmetries and disfigurement.…”
Section: Discussioncontrasting
confidence: 58%
“…3,12 OF/RO usually affects the long bones, ribs, and pelvis, 6 whereas jaw bone involvement is a very rare manifestation of the disease. 12,22 There is no significant sex predilection, and adult patients are the most affected, although our study found a female prevalence (female-tomale ratio 1.66:1) and a 12 year old affected by the lesion. The pathologic process often involves the jaws diffusely, as illustrated in 3 of our reports, possibly leading to severe facial asymmetries and disfigurement.…”
Section: Discussioncontrasting
confidence: 58%
“…16 Furthermore, Kakade et al in 2015 reported a case of ROD in a patient with secondary HPT. 4 Radiographic findings of all cases demonstrated similar clinical and radiographic features such as ground-grass appearance, loss of trabecular pattern, and diffuse swelling of the maxilla and mandible. However, the majority of cases of severe jaw enlargement associated with HPT failed to return to normal contours even after renal transplantation.…”
Section: Case Reportmentioning
confidence: 69%
“…It can occur as a complication of CRF as a result of ROD. [4][5][6][7][8][9][10][11] ROD is a frequent long-term complication of renal disease that can induce a broad spectrum of bone metabolism disorders associated with different pathogenic pathways. The symptoms of ROD comprise bone demineralization with trabeculation and cortical loss, giant cell radiotransparencies, or metastatic calcifications of the soft tissues.…”
Section: Case Reportmentioning
confidence: 99%
See 1 more Smart Citation
“…PTH level increases when the serum calcium concentration is low, such as when calcium intake is lacking or when very low vitamin D levels inhibit sufficient enteral calcium uptake, and in the case of chronic kidney disease. 1,2 In general, PTH attempts to elevate serum calcium levels by stimulating renal calcium reuptake, enteral calcium uptake, and bony calcium release. The effects of PTH can vary according to the age of the patient, the serum PTH concentration pattern, and the skeletal site.…”
mentioning
confidence: 99%